Removal of Ammonium and Phosphate from Synthetic Wastewater of Complex Fertilizer Industry Through Struvite Crystallization Process - Zulfikar Luthfi, Muhammad; Setiadi, Tjandra; Nury, Dennis Farina; Choerudin, Choerudin (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2023)
The complex fertilizer industry produces wastewater which contributes to the pollution of water bodies because it contains high levels of phosphate and ammonium concentrations and high TKN (Total Kjeldahl Nitrogen) which contains organic nitrogen. The organic nitrogen contained in the complex fertilizer wastewater is urea so it can be hydrolyzed to ammonium using the urease enzyme. The ammonium formed from the hydrolysis of urea will then react with magnesium and phosphate to form struvite, a crystal of Magnesium Ammonium Phosphate (MAP). The purpose of this study was to determine the effect of aeration and the enzyme urease in the removal of ammonium and phosphate in complex fertilizer synthetic wastewater through struvite precipitation. Struvite precipitation was carried out in a batch reactor which had a working volume of 0.5 L with variations in aeration rate, aeration time, and the addition of urease enzyme from Jack bean peas (Canavalia ensiformis). Residual ammonium and phosphate levels were analyzed and struvite crystal formation (MAP) was determined using Scanning Electron Microscope (SEM) and X-ray diffraction (XRD). The results showed that the aeration reactor was able to form struvite crystals and remove the ammonium and phosphate content in the synthetic wastewater of complex fertilizers. The removal of ammonium with a molar ratio of [Mg2+] : [NH4+] : [PO43-] 1:2:1 reached 61-77% at high aeration rates because a lot of ammonium was released into the air. The phosphate removal reached 99%. The urease enzyme was proven to be able to hydrolyze urea into ammonium and increase the pH value and affect the shape of the resulting struvite crystals. The precipitate product obtained was struvite crystals which were confirmed by analysis using SEM-EDX and XRD.